Personality Traits, Perception of Social Support and Motivation of Achievement as Predictors of Academic Performance in Students Belonging to Programs of Inclusion and Permanence in University Education (Pace) [Rasgos de Personalidad, Percepción de Apoyo Social y Motivación de Logro Como Predictores del Rendimiento Académico en Estudiantes Pertenecientes a Programas de Inclusión y Permanencia en la Educación Universitaria (Pace)] - Morales-Navarro, M; Baeza-Ugarte, C (Universidad de Chile, 2019)
We present the results of an investigation whose objective was to study how certain personal variables (personality traits, perception of social support and motivation for achievement) of students can explain the academic performance, specifically in students belonging to an accompaniment program for access to higher education (PACE). There was a non-probabilistic and incidental sample of 155 university students from a public university during the first semester. The results show that there are no significant differences between men and women regarding the variables studied. In addition, there were significant correlations between academic performance and motivation for achievement, social support from the nearby network (friends), the perception of family support, and with the personality trait open to experience. Through a multiple linear regression, it was obtained that the personal variables of this study can explain 33.3% of the variance in academic performance. The need arises to deepen about these factors that are associated with the university permanence of students from vulnerable sectors. © 2019 Universidad de Chile. All rights reserved.